Pengaruh Profitabilitas dan Keputusan Investasi terhadap Harga Saham dengan Mediasi Kebijakan Dividen Perusahaan Energi (Migas dan Batubara) di BEI 2022-2025 - Carolina Santyanuari; Sigit Puji Winarko; Andy Kurniawan (Kajian Ekonomi dan Akuntansi Terapan, 2026)
This study aims to analyze the effect of return on assets (ROA) and investment decisions (PBV) on stock prices (closing prices) using dividend policy (DPR) as a mediating variable in energy sub-sector companies (oil and gas and coal) listed on the Indonesia Stock Exchange for the period 2022-2025. A quantitative approach was employed using path analysis from the Hayes PROCESS macro in SPSS. The sample was selected using a purposive sampling technique from energy sub-sector companies. The results show that profitability (ROA) has a positive and significant effect on stock prices, and investment decisions (PBV) also have a positive and significant effect on stock prices. Dividend policy (DPR) is shown to have a negative and significant effect on stock prices. In its mediating role, dividend policy is shown to mediate the effect of investment decisions on stock prices, but cannot significantly mediate the effect of profitability on stock prices. These findings emphasize that investors and company management need to pay attention to profitability and the quality of investment decisions as fundamental factors in stock price movements in the energy sector.